Green manure, a sustainable strategy to improve soil quality: a case study in an oxisol from northern Brazil - Pimentel, Marcelo Laranjeira [UNESP]; Reis, Iolanda Maria Soares; Romano, Maria Lita Padinha Corrêa; de Castro, Jailson Sousa; Vildoso, Carlos Ivan Aguilar; Gasparin, Eloi; de Sia, Eliandra Freitas; de Sousa, Leandro Silva (Southern Cross Publishing, 2023)
Cassava (Manihot esculenta Crantz) is an easy to manage crop with good tolerance to drought and low-fertility soils. Although chemical fertilization is known to improve cassava yield, little is known about the potential of legume green manures to enhance soil chemical properties and consequently increase crop production. Here we analyze how different legume green manures affect cassava root growth and soil quality in an oxisol from northern Brazil. In this field study, we evaluated the effect of four green manure treatments (no fertilization, Crotalaria, jack bean, and cowpea) on soil exchangeable cation contents, pH H2O, pH KCl, ΔpH, exchangeable aluminum, sum of bases (SB), cation-exchange capacity (CEC), soil organic carbon (SOC), plant diameter, plant height, and root yield. Cowpea treatment was the most effective in increasing exchangeable cations, CEC, SB, and root yield, whereas jack bean treatment increased acid cations and SOC. A hierarchy of exchangeable cations was observed, Ca2+>Mg2+>K+, a result likely associated with nutrient absorption by cassava plants. Plant diameter had a positive linear correlation with root yield. Overall, our results indicate that green fertilization positively influences SOC, minimizing the depletion of exchangeable cations and thereby preventing yield losses. Cowpea treatment, however, acted more broadly on the variables studied.
Keywords: Acidic soil; Green fertilization; Manihot esculenta; Soil fertility; Soil Organic Matter